Modification Effect of Volume Cylinder Four Stroke Engine to Effective Power - Najamudin NAJAMUDIN (International Conference on Engineering and Technology Development (ICETD), 2014)
To improve the ability, power changes (performance) of a motor used for racing most mechanics do modifications to the cylinder volume. When the motor cylinder enlarged, the enlarged combustion volume, so that automatically will increase the compression ratio and compression pressure effect on the combustion pressure rise as well, in order to obtain great power. Bore up is a way to increase the volume of the contents of the cylinder, using a piston that has a larger diameter than the standard. So that the cylinder and piston are enlarged, the fuel and air for combustion in the engine can be more obtainable with high compression ratio that produces greater energy (torque) and a higher engine speed (rpm). In the discussion of this study the author discusses the influence of bore up the engine on the motorcycle supra x-cylinder 125 cc of cylinder diameter 52.4 mm to 54 mm, the things that need to be reviewed in this discussion include: Changes in power (performance), changes in torque before and after the engine in the bore up.